Estimating total allowable catch and mapping potential fishing zones for tuna in the Flores Sea: A remote sensing-geographic information system perspective - Mukti Zainuddin; M. Banda Selamat; Muhammad Ridwan; Sarip Hidayat; Achmar Mallawa (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2015)
Flores Sea is one of the most potential tuna fishing grounds in Indonesia. However, the information about potential stock, distribution and abundance of tuna in that area is little known. The objectives of this study were to estimate the Total Allowable Catch (TAC) and to map the potential pelagic fishing zones for tuna dominated by yellowfin tuna in the Flores Sea. Firstly, the Maximum Sustainable Yield (MSY) was estimated using Surplus Production Model and then the TAC was calculated using the 80% of the MSY. The six years’ time series data (2008-2013) of catch and fishing effort data were used for this study. Secondly, satellite images of sea surface temperature (SPL) and chlorophyll-a together with catch data were used to map out the potential predicted area based on the level of probability of their preferred oceanographic ranges for the period of October-December 2013. Results indicated that the exploitation rate for tuna was approximately 55% of the TAC (44 % of MSY level) on average during the last 6 years. The Potential predicted fishing zones for tuna well formed in December, and mostly occurred in the surrounding waters of the Selayar main island and from the areas of south western Jampea, Kayuadi, and Tarupa Islands to the north eastern area of the Flores Sea. These results were consistent with the empirical data. As a result, to exploit tuna resources optimally at the TAC level, this study recommended that the fishermen utilize the potential fishing zones defined by the preferred area of both SST and chlorophyll-a. These findings suggested that the potential fishing zone maps constructed from satellite images provided important information to locate spatially and temporally potential tuna fishing zones in the Flores Sea. Abstrak Laut Flores merupakan salah satu daerah potensial penangkapan tuna di Indonesia, namun informasi potensi, distribusi dan kelimpahannya belum banyak diketahui. Tujuan penelitian ini adalah untuk mengestimasi potensi sumber daya ikan tuna yang dinyatakan dalam jumlah tangkapan yang diperbolehkan (JTB) dan memetakan zona potensi penangkapan ikan (ZPPI) tuna tersebut (didominasi oleh ikan tuna madidihang) di Perairan Laut Flores. Analisis dikembangkan dalam dua tahap, pertama mengestimasi hasil tangkapan maksimum lestari (MSY) dan JTB menggunakan enam tahun data time series produksi dan upaya penangkapan (2008-2013), dan kedua, data satelit suhu permukaan laut (SPL) dan klorofil-a digunakan untuk memetakan ZPPI tuna berdasarkan tingkat probabilitas kesesuaian faktor oseanografi terha-dap kelimpahan ikan tuna pada periode musim puncak Oktober-Desember 2013. Hasil penelitian menunjukkan bahwa tingkat pemanfaatan sumber daya ikan tuna di Laut Flores adalah 55% dari JTB atau 44% dari MSY berdasarkan pro-duksi rata-rata enam tahun terakhir. Formasi ZPPI tuna paling produktif ditemukan pada bulan Desember di sekitar per-airan Selayar dan dari perairan barat daya Pulau Jampea, Kayuadi, Tarupa hingga ke timur laut Laut Flores. Hasil pre-diksi ZPPI ini konsisten dengan data lapangan. Untuk mengeksploitasi potensi tuna secara optimal di Laut Flores pada level JTB, nelayan diharapkan beroperasi pada ruang dan waktu yang tepat di ZPPI tersebut. Penelitian ini menyajikan informasi spasial dan temporal tentang lokasi ZPPI tuna yang divisualisasi dari data satelit untuk mendeteksi keberada-an dan kelimpahan ikan tuna pada musim puncak di Laut Flores.